KINERJA ENZIM GANDA PADA PRETREATMENT MIKROALGA UNTUK PRODUKSI BIOETANOL - Padil, Padil; Syamsiah, Siti; Hidayat, Muslikhin; Kasiamdari, Rina Sri (Jurnal Bahan Alam Terbarukan, 2016)
The use of biomass of microalgae as a feedstock to produce bioethanol is very promising, it is caused by a large amount of carbohydrates contained in microalgae physiology cell. The main obstacle of enzymatic hydrolysis in order to produce bioethanol is the bound starch granules in a rigid cell wall. Therefore, pre-treatment steps needed to remove and convert complex carbohydrates into simple sugars before the fermentation process. Tetraselmis Chuii microalgae species are green microalgae (Chlorophyta) in which the cell wall containing cellulose and hemicellulose as the main constituent, therefore, this study observe the effect of the use of cellulase enzymes and xylanase as a strategy to open up the cell walls of microalgae. Another investigated parameter is the enzyme concentration, temperature, pH, and methods of use of enzymes. The results showed that the highest yield of glucose obtained was 31.912% (w / w) and is achieved under the conditions of a temperature of 45oC, pH of 4.5, the amount of biomass of microalgae as 5 g/L, the concentration of cellulase enzymes and xilanase 30% (w / w) at 40 minute at mechanism using cellulase and xylanase enzymes simultaneously.